Correlation of E23K gena KCNJ11 polymorphism as a Risk Factor for Obesity with Type 2 Diabetes Mellitus In Jayapura, Papua - Maay, Jems K. R.; Hastuti, Pramudji; Sadewa, Ahmad H. (International Journal of Research in Medical Sciences, 2021)
Background: Pathophysiology of type 2 diabetes mellitus (T2DM) is influenced by the complex interaction of several genes that regulate energy metabolism in the body. Several polymorphisms that occur in many gene encode components of glucose metabolism regulation are significantly implicated in the onset of T2DM. Methods: This case-control study. Case group with 58 subjects of T2DM patients with obesity and a control group with 58 subjects of non-DM obese patients from ethnic Papuans in Jayapura city, Indonesia. Results: The results of the genotype frequency distribution (AA, GA, GG) and allele (A and G) showed statistically no significant differences. The relationship of anthropometry and blood chemical parameters with genotype (AA-GA-GG) gene potassium inwardly rectifying channel sub family J member 11 (KCNJ11) showed no statistically significant difference (p>0.05). The relationship of anthropometry and blood chemical parameters of genotype (AA-GA) gene KCNJ11 indicated that diastolic blood pressure variables, glucose, triglyceride, high density lipoprotein (HDL), insulin levels, homeostatic model assessment (HOMA) β, and insulin resistance (IR) had statistically significant differences. Conclusions: There is no difference in frequency between genotypes and alleles of the gene KCNJ11 in the T2DM and non-DM group with obesity. There is a link between genotypes of the gene KCNJ11 and T2DM occurrence. As for the combined analysis between blood chemical parameters and genotypes of gene KCNJ11, there is a relationship between genotypes of the gene KCNJ11 and the incidence of T2DM in LDL variables, where the coefficient interval value increases in patients with T2DM.